Screw Conveyor Rotor Multi-objective Optimization Design - ZHANG Yuan; JIANG Xiao-han; FAN Hua-ping; LI Xi-han (Journal of Harbin University of Science and Technology)
Aiming at the optimization problem of the rotor of spiral conveyor structure of Pill making machine of Chinese Medicine when it worked in a complex environment easily lead to deformation which was caused by the low frequency coupling vibration from other parts′ vibration interference, using the finite element method for modal analysis. A parameterized association model was set up, spiral rib width and the rotor radius were refered as the correlated parameters.The response surface method was used to optimize the natural frequency and shape variables. The optimized rotor deformation can be reduced to 65% of the original model and the frequency is increased by 13%. Improving the natural frequency of the rotor under the constraint condition can effectively avoid the low frequency coupling vibration of the rotor, and extend the service life of the small Chinese medicine decocting and pelletizing machine.